Stratigraphic expression of the Paleocene-Eocene Thermal Maximum climate event during long-lived transient uplift—An example from a shallow to deep-marine clastic system in the Norwegian Sea - Sømme, Tor O.; Huwe, Simone Isabelle; Martinsen, Ole J.; Sandbakken, Pål Trygve; Skogseid, Jakob; Valore, Lucas A. (Frontiers in Earth Science, 2023)
Seismic geomorphology and stratigraphic analysis can reveal how source-to-sink systems dynamically respond to external climatic and tectonic forcing. This study uses seismic reflection data from the Norwegian Sea to investigate the stratigraphic response to a short-lived (0.2 Myr) phase of climate change during the Paleocene-Eocene Thermal Maximum (PETM), superimposed on a long-lived (~8 Myr) phase of hinterland uplift. Long-term margin uplift resulted in ~300 m relative sea-level fall, forced regression and formation of incised valleys during latest Paleocene-earliest Eocene. The short-lived PETM climate perturbation changed the transport dynamics of the system, allowing sediment to be bypassed to wide channel complexes on the basin floor, feeding a large mud-rich basin-floor fan more than 50 km into the basin. After the PETM, sediments were again deposited in toe-of-slope aprons closer to the shelf break. Maximum regression around 55-56 Ma resulted in the formation of a subaerial unconformity. The style of subaerial incision, valley and canyon formation were dictated by shelf accommodation and proximity to the area of direct sediment input. Out-of-grade shelves and slopes sourced by littoral drift were prone to incision, but direct-fed and graded shelves and slopes were not. Despite maximum regression, sediments were not transported significantly beyond the toe-of-slope aprons, suggesting that rapid climate fluctuations were more efficient in bypassing sediment to the deep-water than low stands of sea level. As long-term accommodation increased after the PETM, deltas were still able to reach shelf edge, but periods of maximum regression were not associated with deep incisions along the outer shelf and only smaller canyons and gullies formed. Accommodation continued to increase in early Eocene and sediments were captured and stored on the shelf in aggrading topsets, preventing significant bypass to the toe-of-slope. The shelf-slope wedge was finally transgressed at around 51 Ma. The age of deep valley incisions overlaps with the time of subaerial erosion in the East Shetland and Faroe-Shetland basins, suggesting a common driver for North Atlantic uplift around 55-56 Ma. This study demonstrates the high-resolution stratigraphic response to long and short-term external forcing together with intrinsic processes and can help identify similar relationships in other areas.